MENINGKATKAN NILAI PERUSAHAAN MELALUI INVESTASI TEKNOLOGI INFORMASI - Wahyu Wiyani (Jurnal Keuangan dan Perbankan, 2008)
Adopting information technology is a necessary requirement for conducting anybusiness in such globalized competitive era. Using the innovative information technologywill give the chance for a firm to become the winner from the competition cause the firm canwork efficiently and effectively, it can increase performance so that it can boots its firm value.